UNSALVAGEABLE EYE: HOW CAN WE DO MORE? Poster Presentation - Case Report - General practitioner - Jessica Jovia; Gladys Kusumowidagdo; Randy Sarayar; Hisar Daniel (Majalah Oftalmologi Indonesia, 2023)
Introduction : Unsalvageable eye, consisting of total visual loss, orbital wall fracture, and disfigured globe, is devastating for both patients and caretakers. This impairment is a challenge for ophthalmologists to manage. Although visual rehabilitation is impossible, the appropriate management results in outcome that would improve patient’s quality of life (QoL). We aim to report our successful case of orbital reconstruction with satisfactory outcome. Case Illustration : A 75-year-old male presented to our clinic with total visual loss of right eye (RE) after motorcycle accident three months prior. Examination revealed phthisical RE, partially-healed full-thickness inferior palpebral laceration, and inferomedial blow out fracture (BOF). Electroretinography and visual evoked potential examination showed a decrease of right optic nerve conduction. The patient expressed discontentment with his current physical condition. Simultaneous procedures of orbital floor and medial wall fracture repair using silicone block followed by lid reconstruction, and mucous membrane grafting for ocular surface were performed. An ocular prosthesis was fitted. The patient was pleased with the outcome. Discussion : Ophthalmologists are often left with little room to aid patients with this condition. More can be done to unsalvageable eye cases. This case shows that improvement of patient’s QoL can be achieved by orbital reconstruction and ocular prosthesis fitting. Conclusion : The main objective of managing unsalvageable eye is to restore patient’s orbital anatomical features, hence, improving his QoL.